Research on the Protection and Inheritance of Ethnic Minority Costumes From the Perspective of Intangible Cultural Heritage - Gao, Jianping; Xu, Feifei (International Journal of Mechanical and Electrical Engineering, 2024)
Ethnic minority clothing refers to clothing with unique characteristics of ethnic minorities. Ethnic minorities have rich clothing culture and living habits, and their production techniques are diverse and unique. As traditional handicrafts, with the development of modern society, some traditional handicrafts face severe inheritance problems. Therefore, it is urgent to protect them and they have historical responsibilities. Of course, the value of inheritance is immeasurable. In this article, I take the characteristics of ethnic minority clothing as the starting point and propose specific protection and inheritance strategies, aiming to provide some valuable reference suggestions for the protection and inheritance of ethnic minority clothing.